The global implications of U.S. withdrawal from WHO and the USAID shutdown: challenges and strategic policy considerations - Auwal Rabiu Auwal; Abubakar Sunusi Ishak; Shuaibu Saidu Musa; Abbas Musa; Abubakar Saadu; Anila Riaz (Frontiers in Public Health)
The U.S. withdrawal from the WHO and the shutdown of USAID disrupt global health governance, threatening disease surveillance and reversing progress made in combating HIV/AIDS, tuberculosis, and malaria through initiatives like PEPFAR. The WHO's central role in coordinating global health responses, exemplified by its leadership in the COVAX initiative, is critical to pandemic preparedness and equitable vaccine distribution. The disengagement decision undermines humanitarian relief efforts, particularly in fragile states where U.S. contributions are vital for food security, education, and healthcare. This policy brief outlines actionable recommendations to mitigate the risks of U.S. disengagement, focusing on regional health capacity-building, public-private partnerships, and the continuation of critical investments in global health systems.